A Proposal for an Anthropic Indicator Based on Amazon Community Analysis - Santos Fernandes, José Guilherme dos; Seruffo, Marcos César da Rocha; Souza, Daniel da Silva; Portela, Otávio Rios (International Journal of Advanced Engineering Research and Science, 2022)
This work aims to produce indicators according to the perception of residents of communities and ecosystems of the Amazon biome, through the collection and analysis of the results of a form in which they express their impressions about events and practices of anthropization. The results found allowed the application of the analytical method of decision making (Analytic Hierarchy Process – AHP), to indicate the degree of anthropization of the people surveyed on a hierarchical scale, according to the syntagma of the three ordering axes of the themes of the form. The contribution allows the generation of correlation models, which help the understanding of the relationship between humans and the environment and the level of anthropic perception of those involved.